Adopsi Penggunaan Layanan Digital Fintech pada Generasi X di Indonesia - Alisia, Siti Noor; Puspawati, Dewita (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
This study aims to analyze the impact of effort expectancy, perceived enjoyment, and performance expectancy on behavioral intention through customer satisfaction in the use of digital fintech services, with a particular focus on Generation X (ages 44-59). Data were collected through a questionnaire adapted from the Unified Theory of Acceptance and Use of Technology (UTAUT) model, involving 175 Generation X respondents in Indonesia. The sampling method used was non-probability sampling with a purposive sampling technique. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM PLS) with Smart PLS software. The results of the study show that perceived enjoyment does not have a significant effect on behavioral intention, and effort expectancy does not significantly affect customer satisfaction. However, effort expectancy, performance expectancy, and customer satisfaction have a significant effect on behavioral intention. Perceived enjoyment and performance expectancy significantly influence customer satisfaction. On the other hand, effort expectancy does not significantly affect behavioral intention through customer satisfaction, while perceived enjoyment and performance expectancy significantly affect behavioral intention through customer satisfaction